Advances in computers., - Zelkowitz, Marvin V., 1945- (Advances in Computers Ser., 2005)
This present volume describes some of the latest advances in the computer science field today. This current volume emphasizes information processing with chapters on artificial intelligence, data bases and software engineering. In particular it looks at the interfaces between AI and software development with chapters on how AI affects the development of correct programs, and conversely, how software engineering can affect the development of correct AI programs. Key Features: * In-depth surveys and tutorials on new computer technology. * Well-known authors and researchers in the field. * Extensive bibliographies with most chapters. * Impact of AI on software development and impact of software development on correct AI programs. * What is the educational role of mathematics in the development of the next generation of computer professional? * In-depth surveys and tutorials on new computer technology. * Well-known authors and researchers in the field. * Extensive bibliographies with most chapters. * Impact of AI on software development and impact of software development on correct AI programs. * What is the educational role of mathematics in the development of the next generation of computer professional?